ANALISIS USAHATANI KENTANG (Studi Kasus di Desa Pulosari Kecamatan Pangalengan Kabupaten Bandung) - Kundrat; Lily Sumarti; Rimelke Rahmadia Febryane; Sholehah Nurhasanah (Program Studi Agroteknologi Faperta UNIBBA, 2026)
Abstract Potatoes are a superior horticultural commodity with high economic value and are widely cultivated in Pulosari Village, Pangalengan District, Bandung Regency. This study aims to analyze the amount of revenue and income, and evaluate the level of business feasibility through the R/C ratio and Break Even Point (BEP) approaches in potato farming. The method used is descriptive quantitative with primary data collection through direct interviews with farmers using questionnaire instruments. While secondary data is sourced from literature and related agencies. Respondents in this study were potato farmers who are members of the Anugerah Farmers Group, totaling 30 people. The results showed that the total production cost of potato farming reached Rp. 100,011,470.58 per hectare per planting season with a total revenue of Rp. 173,756,964.71 per hectare per planting season, so that the income obtained was Rp. 73,745,494.13 per hectare per planting season. The R/C Ratio value of 1.74 means that every expenditure of Rp1.00 produces revenue of Rp. 1.74, meaning that potato farming in Polusari Village, Pangalengan District, Bandung Regency, is profitable. Break-Even Point (BEP) analysis shows a production break-even point of 9,524.90 kg, and a price break-even point of Rp. 6,043.62 per kilogram. These findings confirm that potato farming in Pulosari Village is efficient, productive, and has the potential for sustainable development.